2013
DOI: 10.1111/jocd.12033
|View full text |Cite
|
Sign up to set email alerts
|

Combination of herbal extracts and platelet‐rich plasma induced dermal papilla cell proliferation: involvement of ERK and Akt pathways

Abstract: In this study, we have shown that combination of herbal extracts and PRP plays an active role in promoting the proliferation of human dermal papilla (DP) cells via the regulation of ERK and Akt proteins, and this may be applicable to the future development of herbal extracts and PRP combination therapeutics to enhance hair growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 29 publications
1
22
0
2
Order By: Relevance
“…These cells are not only essential for hair development but behave also as a reservoir with the potential to differentiate and regenerate the multiple layers of the outgrowing shaft 21. These results are consistent with other studies that have highlighted the mitogenic potential of platelet-rich plasma over bulbar cells, by means of extracellular signal kinases/Akt pathway activation and CDK4/cyclin D1 overexpression 22. Fibroblast growth F I G U R E 6 Representative micrographs of H&E-stained hair grafts showed a significant reduction in the interstitial edema during PRGF preservation comparing to control treatment (A-B).…”
supporting
confidence: 91%
“…These cells are not only essential for hair development but behave also as a reservoir with the potential to differentiate and regenerate the multiple layers of the outgrowing shaft 21. These results are consistent with other studies that have highlighted the mitogenic potential of platelet-rich plasma over bulbar cells, by means of extracellular signal kinases/Akt pathway activation and CDK4/cyclin D1 overexpression 22. Fibroblast growth F I G U R E 6 Representative micrographs of H&E-stained hair grafts showed a significant reduction in the interstitial edema during PRGF preservation comparing to control treatment (A-B).…”
supporting
confidence: 91%
“…Few studies have attempted to explain the mechanism by which PRP induces the proliferation of HDFs, as it relates to intracellular signaling. For example, in one study, it was reported to enhance angiogenesis through angiopoietin 1‐Tie2 or promote cell proliferation by controlling ERK or Akt . Moreover, a recent study showed that PRP promotes the proliferation of HDFs through the activation of ERK1/2 signaling; this was shown by the fact that PRP promotes ERK1/2 phosphorylation, whereas ERK1/2 inhibition eliminates the increase in proliferation triggered by PRP .…”
Section: Discussionmentioning
confidence: 99%
“…3 Therefore, alternative hair loss treatments are needed. 4 Recently, it was reported that injection of platelet-rich plasma (PRP) into mice induces hair growth, indicating that PRP helps to maintain the hair and scalp, and stimulates hair follicle activity, thereby encouraging hair growth.…”
Section: Introductionmentioning
confidence: 99%